(untitled) (International Journal of Food and Nutritional Sciences, 2021)
This study delves into the multifaceted challenges confronted by widows in India, examining distinct dimensions such as legal, economic, healthcare, educational, and societal realms. Within the legal framework, the research identifies gaps, particularly in inheritance laws and discrimination, proposing reforms to secure unambiguous inheritance rights and enact anti-discrimination measures. Economically, the focus is on empowering widows through targeted vocational training, financial inclusion policies, and advocating for employment quotas to enhance self-reliance. Health disparities are addressed through awareness campaigns, community-based healthcare initiatives, and policy measures aimed at closing existing gaps. Social support emerges as a critical factor, with recommendations for community-based programs and initiatives by governmental and non-governmental organizations to combat the isolation often experienced by widows. Additionally, cultural norms are targeted through advocacy efforts, including media campaigns, educational programs, and dialogue with religious institutions.These findings provide a foundation for proposed recommendations, offering a strategic pathway for interventions and policy initiatives. The study seeks to not only raise awareness but also contribute to actionable solutions, emphasizing the dynamic nature of responses required to address the evolving challenges faced by widows in India. Ultimately, the goal is to empower widows and foster a society that is more equitable and compassionate.